Validating satellite derived and modelled sea-ice drift in the Laptev Sea with in situ measurements from the winter of 2007/2008 - Rozman, Polona; Hölemann, Jens A.; Krumpen, Thomas; Gerdes, Rüdiger; Köberle, Cornelia; Lavergne, Thomas; Adams, Susanne; Girard-Ardhuin, Fanny (Polar Research, 2011)
A correct representation of the ice movement in an Arctic sea-ice-ocean coupled model is essential for a realistic sea-ice and ocean simulation. The aim of this study is to validate the observational and simulated sea-ice drift for the Laptev Sea Shelf region with in situ measurements from the winter of 2007/08. Several satellite remote-sensing data sets are first compared to mooring measurements and afterwards to the sea-ice drift simulated by the coupled sea-ice-ocean model. The different satellite products have a correlation to the in situ data ranging from 0.56 to 0.86. The correlations of sea-ice direction or individual drift vector components between the in situ data and the observations are high, about 0.8. Similar correlations are achieved by the model simulations. The sea-ice drift speed derived from the model and from some satellite products have only moderate correlations of about 0.6 to the in situ record. The standard errors for the satellite products and model simulations drift components are similar to the errors of the satellite products in the central Arctic and are about 0.03 m/s. The fast-ice parameterization implementation in the model was also successfully tested for its influence on the sea-ice drift. In contrast to the satellite products, the model drift simulations have a full temporal and spatial coverage and results are reliable enough to use as sea-ice drift estimates on the Laptev Sea Shelf.